DAMPAK PANDEMI COVID-19 TERHADAP LOYALITAS PELANGGAN PADA MCDONALD’S CABANG SHINTA KARAWACI - Andres Dharma Nurhalim (STIE Wiyatamandala, 2021)
The fast food industry is one of the sectors affected by the COVID-19 pandemic. The prohibition of large-scale social interaction in the community, such as holding meetings during the Large-Scale Social Restrictions (PSBB) established by each region, also contributed to a sharp decline in food and beverage sales. The average result of the COVID-19 pandemic impact variable questionnaire (X) at McDonald's Shinta Karawaci Branch was 68% in the good category. Of all the indicators of the statement, it can be seen that the lowest indicator is